Synthesis of Monosulfated Lewis a Trisaccharide Library Through Sulfation of a Partial Protected Trisaccharide - Ding, Yili; Wang, Bingyun (Letters in Organic Chemistry, 2017)
Background: The biological significance of glycoconjugates has stimulated much synthetic activity in oligosaccharide synthesis, the sulfate group in sulfated oligosaccharides has been shown to be constitutively involved in the interaction of ligands with selectins, establishing combinatorial methods for the synthesis of sulfated oligosaccharide library may be useful for screening of ligands of selectins. Results: Random sulfation of a partial benzyl protected Lewis A trisaccharide in pyridine provided a sulfated trisaccharide mixture. After hydrogenation with Pd/C and purification on Sephadex A-50 column, a monosulfated trisaccharide library was obtained as a mixture. The H-H COSY NMR spectrum of this mixture showed that this mixture contains all five possible monosulfated Lewis A trisaccharides with acceptable ratio. Conclusion: Random sulfation of a partial protected oligosaccharide was demonstrated as the most efficient method so far for the synthesis of monosulfated oligosaccharide library.
Keywords: sulfated oligosaccharide library